Opaque intraocular lens for intractable diplopia: experience and patients' expectations and satisfaction. Issue 7 (12th June 2008) - Hadid, O H; Wride, N K; Griffiths, P G; Strong, N P; Clarke, M P
Abstract : Aim: To report the authors' experience with the use of opaque intraocular lenses (IOL) in diplopia unresponsive to traditional management strategies, and to assess patients' satisfaction and the visual function of patients following insertion of opaque IOL using the Visual Function Index (VF-14). Settings: Royal Victoria Infirmary, Newcastle upon Tyne, UK. Method: Data were obtained on all patients who underwent insertion of an opaque IOL at our institution between 2002 and 2006. Patients were interviewed by telephone. Any visual function impairment was assessed using the VF-14 questionnaire. Patients were also asked to score subjectively their overall satisfaction with the visual outcome after opaque IOL insertion. Results: The authors studied 12 patients (n = 12) who had insertion of opaque IOL. All patients had constant and persistent diplopia unresponsive to other treatments acceptable to the patient. The median duration of diplopia was 5.5 years (interquartile range was 2.4–17.3 years). The postoperative VF-14 ranged from 75 to 100, and the mean VF-14 was 91 (95% CI 83–99). Three patients reported a maximum score of 100. Patient satisfaction ranged from 2 to 4, and the average was 3.4 out of 4. Conclusions: Opaque IOL insertion is a valuable option in the management of intractable diplopia. The VF-14 revealed very little or no impairment in visual function following the procedure. All patients reported improvement in their visual function and were pleased with the final outcome.